Escape room para promover el aprendizaje centrado en el estudiante en la asignatura de historia de segundo bachillerato, de la unidad educativa “Carlos María de la Condamine”, período 2021-2022 - Quisnancela Machado, Carmen del Rocío (2023)
ABSTRAC The present work is born from the problems found in the educational unit Carlos María de la Condamine; which is summarized in that teachers lack knowledge for the creation of Escape Room for the development of the skills of the subject of history in the second year of high school students. Faced with this problem, the following objective is proposed to create a didactic proposal based on the Escape Room gamification technique, as a student-centered learning strategy in the history subject of the second baccalaureate, for the achievement of the same the respective consultation has been carried out literature that lays the theoretical foundations of this research. The methodological approach of this work is quantitative and a quasi-experimental design, with a field and cross-sectional typology; this through a propositional level, which includes the deductive method; After this, the didactic guide was built based on the Escape Room gamification technique, which incorporates exercises that can strengthen the skills of the history subject. This allowed the application of a questionnaire to diagnose the level of digital skills that students have to use technological gamification tools through Escape Room strategies. The results obtained in the diagnostic stage allowed us to conclude that students in the field of communication, although they know how to use social networks, not all of them handle emails correctly and do not maintain correct behavior when sharing information and messages; There is also evidence of a positive development with the implementation of the guide in the teaching work of the classroom. In order to improve the management of digital skills and to strengthen the development of history subject skills, a guide with exercises that apply the Escape Room strategy was designed. Keywords: Escape Room, student-centered learning, History, gamification.